Anifrolumab Study for Treatment Effectiveness in the Real World (ASTER) among patients with systemic lupus erythematosus: protocol for an international observational effectiveness study - Marta Mosca; Stephanie Chen; Heide Stirnadel-Farrant; Cathy Emmas; Lucy Carty; Caroline Seo; Alessandro Sorrentino; Cassandra Nekeman-Nan; Samuel Chen; Miina Waratani (BMJ Open)
Introduction Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a diverse clinical presentation that involves multiple organ systems and may lead to organ damage and increased risk of mortality. SLE is associated with a high burden of disease that can include loss of productivity and employment and reduced health-related quality of life. The current standard of care for SLE is primarily based on immunosuppression and glucocorticoids and is associated with risk of toxicities and poor tolerability. Anifrolumab, a human monoclonal antibody to type I interferon receptor subunit 1, was recently approved as a new treatment for patients with moderate-to-severe SLE.Methods and analysis Here, we report the study design of the ongoing, multinational Anifrolumab Study for Treatment Effectiveness in the Real World (ASTER) that includes 3-years of follow-up beginning with the first infusion of anifrolumab and 1 year of retrospective baseline data. ASTER aims to enrol 500 adult patients receiving anifrolumab for SLE in Europe and Canada. The key study objective is to describe the real-world effectiveness of anifrolumab in routine clinical practice, including clinician-reported disease activity and patient-reported outcomes collected via mobile application. This mobile application also includes a medication diary, where patients report their prescription and non-prescription medication use for SLE on a weekly basis; these data will lend insights on treatment patterns for the study population.Ethics and dissemination The design of the ASTER study was informed through consultations with patients with SLE who provided important insights to help maximise patient engagement, retention and the collection of key, patient-relevant endpoints. ASTER enrolment began in February 2023 and the study is expected to finish in 2029.Trial registration number NCT05637112.